Rafał Stankiewicz, Koordynacja w prawie administracyjnym, seria Monografie Prawnicze, Wydawnictwo C.H. Beck, Warszawa 2019, ss. 276, ISBN 978-83-8158-273-5 - Jachimowicz-Jankowska, Paulina (Studia Prawa Publicznego, 2021)
Rafał Stankiewicz, Koordynacja w prawie administracyjnym, seria Monografie Prawnicze, Wydawnictwo C.H. Beck, Warszawa 2019 ss. 276, ISBN 978-83-8158-273-5 (opr. Paulina Jachimowicz-Jankowska)